Artificial Intelligence Technique of Synthesis and Characterizations for Measurement of Optical Particles in Medical Devices - Walid Theib Mohammad; Sherin Hassan Mabrouk; Rania Mohammed Abd Elgawad Mostafa; Mohammad Bani Younis; Ahmad Maher Al Sayeh; Mona Abdelmoneim Abdelmabood Ebrahim; Samar Zuhair Alshawwa; Heba Abdelazezm Hassan Ismail; Manal Mahrous Abdalhamed Mohamed; Sara Wans Alshmmry; Malik Bader Alazzam; Md Kawser Ahmed (Applied Bionics and Biomechanics)
The aim of this study is to demonstrate the effect of particle size on semiconductor properties; artificial intelligence is being used for the research methods. As a result, we picked cadmium sulfide (CdS), which is a unique semiconductor material that is employed in a broad variety of current applications. Given that CdS has distinct electrical and optical characteristics, it may be employed in the production of solar cells, for example. Solar cells, as is also well known, have become an essential source of energy in the world. Within the visible range (500-700 nm), we create one layer of bulk CdS and one layer of nano-CdS air bulk CdS air and air nano-CdS air. We used a number of instrumentation methods to investigate the naked CdS nanoparticles, including XRD, SEM-EDX, UV-Vis spectroscopy, TEM, XPS, and PL spectroscopy, among others. The results show that for bulk CdS at normal incidence, the transmittance is T=45, and for nano-CdS with particle size 3 nm, the transmittance is T=85.8, with transverse-electric (S-polarized) and transverse-magnetic (P-polarized) transmittances of TE=75 and TM=80, respectively.